2015
DOI: 10.4278/ajhp.131216-quan-645
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Workplace Health Support is Associated with Employee Productivity

Abstract: Higher perceived workplace health support is independently associated with higher work productivity. Employers may see productivity benefit from wellness programs through improved perceptions of workplace health support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 37 publications
0
59
0
Order By: Relevance
“…For example, in the study by Goetzel et al (50), the ROI was -42% excluding indirect costs but 103% including indirect costs. A systematic review found that PA was related to increased psychosocial health in employees (27) and there is also evidence that such health outcomes reduce presenteeism (67). Furthermore, low PA was found to be related to increased absenteeism (68).…”
Section: Health Economic Evaluationsmentioning
confidence: 99%
“…For example, in the study by Goetzel et al (50), the ROI was -42% excluding indirect costs but 103% including indirect costs. A systematic review found that PA was related to increased psychosocial health in employees (27) and there is also evidence that such health outcomes reduce presenteeism (67). Furthermore, low PA was found to be related to increased absenteeism (68).…”
Section: Health Economic Evaluationsmentioning
confidence: 99%
“…Mental health stigma includes the perception that individuals with mental health disorders are weak, flawed, dangerous and/or socially incompetent (Wahl, 2003) and the desire not to want to be thought of as having these characteristics can deter people from seeking or obtaining help (Hinshaw and Cicchetti, 2000). Chen et al (2015) argue that rates of presenteeism vary with the perceived level of workplace support, with those feeling least supported having higher rates of presenteeism. Individuals with poor mental health are also known to be less likely to be in employment: in the UK in 2004, 74 percent of the working age population was in employment but the comparable figure for people considered disabled by a long term mental illness was only 21 percent (Social Exclusion Task Force, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies to date suggest that individuals with poor health and/or low health perceptions (or self-rated health) are at risk of being or becoming unemployed (Leijten et al, 2015;Robroek et al, 2015;van Rijn, Robroek, Brouwer, & Burdorf, 2014), taking health-related absences (Sundstrup, Jakobsen, Mortensen, & Andersen, 2017;Ubalde-Lopez, Delclos, Benavides, Calvo-Bonacho, & Gimeno, 2017), or reporting reduced work ability and/or productivity loss (de Wit, Wind, Hulshof, & Frings-Dresen, 2018;Koolhaas, van der Klink, de Boer, Groothoff, & Brouwer, 2014;Leijten et al, 2014;Lindegård, Larsman, Hadzibajramovic, & Ahlborg, 2014;Lohela-Karlsson, Nybergh, & Jensen, 2018). Importantly, research also indicates that workplace health support can elevate the productivity of employees, independent of the health profile of employees (Chen et al, 2015). Overall, these findings suggest that while health problems tend to interfere with various dimensions of employment, including productivity and engagement, employers' efforts to initiate and promote various forms of health support in the workplace may offset the degree to which health problems interfere with work.…”
Section: The Role Of Health and Health Perceptions In Employment And mentioning
confidence: 99%